Data on the multilocus molecular phylogenies of the Neotropical fish family Prochilodontidae (Teleostei: Characiformes) - Frable, Benjamin W.; Melo, Bruno F. [UNESP]; Sidlauskas, Brian L.; Hoekzema, Kendra; Vari, Richard P.; Oliveira, Claudio [UNESP] (Elsevier B.V., 2016)
The data presented herein support the article Molecular phylogenetics of the Neotropical fish family Prochilodontidae (Teleostei: Characiformes) (B.F. Melo, B.L. Sidlauskas, B.W. Frable, K. Hoekzema, R.P. Vad, C. Oliveira, 2016) [1], which inferred phylogenetic relationships of the prochilodontids from an alignment of three mitochondrial and three nuclear loci (5279 bp) for all 21 recognized prochilodontid species and 22 related species. Herein, we provide primer sequences, museum voucher information and GenBank accession numbers. Additionally, we more fully describe the maximum-likelihood and Bayesian phylogenetic analyses of the concatenated dataset, detail the Bayesian species tree analysis, and provide the maximum likelihood topologies congruent with prior morphological hypotheses that were compared with the unconstrained tree using Shimodaira-Hasegawa tests. (C) 2016 The Authors. Published by Elsevier Inc. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/40).
Keywords: Phylogenetics; Prochilodontidae; Characiformes; BEAST; Shimodaira-Hasegawa test